2015
DOI: 10.1111/aji.12402
|View full text |Cite
|
Sign up to set email alerts
|

Autoantibodies to Factor XII and Kininogen‐Dependent Antiphosphatidylethanolamine Antibodies in Patients with Recurrent Pregnancy Loss Augment Platelet Aggregation

Abstract: Antibodies to LDC27 and IPP30 markedly increased aggregation of normal platelets stimulated by γ-thrombin. Augmentation of SSPA formation was more frequent in the patients with RPL who were positive for anti-FXII than in the control group (P = 0.003). This study strongly supports the hypothesis that aPE and anti-FXII may cause RPL due to disruption of the normal antithrombotic effects of kininogens and FXII.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 45 publications
1
4
0
Order By: Relevance
“…13 14 This suggests that anti-FXII species that recognize IPP30 in patients with recurrent pregnancy loss may inhibit FXII binding to platelets, which leads to thrombosis and pregnancy loss. Results from our previous study 15 supported this hypothesis and demonstrated that exogenously added polyclonal antibodies against IPP30 markedly increased γ-thrombin-induced platelet aggregation in vitro. Furthermore, it was reported that, in a murine model, anti-FXII infusion (or infusion of anti-IPP30 antibodies) induced placental thrombosis and hemorrhage as well as increased placental apoptosis.…”
Section: Introductionsupporting
confidence: 60%
See 1 more Smart Citation
“…13 14 This suggests that anti-FXII species that recognize IPP30 in patients with recurrent pregnancy loss may inhibit FXII binding to platelets, which leads to thrombosis and pregnancy loss. Results from our previous study 15 supported this hypothesis and demonstrated that exogenously added polyclonal antibodies against IPP30 markedly increased γ-thrombin-induced platelet aggregation in vitro. Furthermore, it was reported that, in a murine model, anti-FXII infusion (or infusion of anti-IPP30 antibodies) induced placental thrombosis and hemorrhage as well as increased placental apoptosis.…”
Section: Introductionsupporting
confidence: 60%
“…17 18 19 We screened patients for aPE because our previous study suggested that 37.5% of patients with recurrent pregnancy loss who were positive for anti-FXII antibodies were also positive for aPE and that these autoantibodies may have similar structures and functions. 15…”
Section: Methodsmentioning
confidence: 99%
“…Since half of the patients with an early miscarriage had antibodies to PE and An V, it was suggested that autoimmune mechanisms could be involved in the development of this pregnancy complication. Previously, it has been shown that the antibodies to PE and An V are possible risk factors for a recurrent miscarriage [ 41 , 42 ]. These results are consistent with a meta-analysis that showed a higher incidence of aPL in women with failed IVF/ICSI cycles than women with successful cycles [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…reported that female mice homozygous for total factor XII deficiency had normal deliveries with normal litter sizes, suggesting that congenital factor XII deficiency is not associated with pregnancy loss. Some studies reported that antibodies against factor XII have a strong significant association with RPL . Therefore, autoantibodies against factor XII rather than factor XII deficiency may be a risk factor for thromboembolism and RPL.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies reported that antibodies against factor XII have a strong significant association with RPL. 24,25 Therefore, autoantibodies against factor XII rather than factor XII deficiency may be a risk factor for thromboembolism and RPL.…”
Section: Discussionmentioning
confidence: 99%